2002
DOI: 10.1080/10428190290006099
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF Administered in Time-sequenced Setting During Remission Induction and Consolidation Therapy of Adult Acute Lymphoblastic Leukemia has Beneficial Influence on Early Recovery and Possibly Improves Long-term Outcome: A Randomized Multicenter Study

Abstract: Sixty-four untreated adult acute lymphoblastic leukemia (ALL) patients were randomized to receive chemotherapy alone, n = 31 or chemotherapy and granulocyte colony stimulating factor (G-CSF), n = 33. During induction patients received G-CSF for 5 days between four weekly Epirubicin+Vcr administrations, starting 36 h after each application and finishing 48 h before the next one with the intention to possibly generate a cell cycle dependent protection of normal hematopoietic progenitors and to stimulate granulop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 20 publications
0
14
0
3
Order By: Relevance
“…Semejante a lo sucedido en la experiencia de Puga y cols en Chile, la disposición de factores estimulantes de crecimiento fue limitada siendo un factor signifi cativo en los éxitos de la terapia de inducción 26 . Algunos autores han referido que su administración puede infl uir en el porcentaje de RC debido a la disminución de los procesos infecciosos severos 27 , pero en general se considera que disminuyen el tiempo de duración de la neutropenia y disminuyen el tiempo de estancia hospitalaria 28,29 . En cuanto al tratamiento de los episodios de neutropenia febril, este se realizó acorde a las consideraciones internacionales.…”
Section: Discussionunclassified
“…Semejante a lo sucedido en la experiencia de Puga y cols en Chile, la disposición de factores estimulantes de crecimiento fue limitada siendo un factor signifi cativo en los éxitos de la terapia de inducción 26 . Algunos autores han referido que su administración puede infl uir en el porcentaje de RC debido a la disminución de los procesos infecciosos severos 27 , pero en general se considera que disminuyen el tiempo de duración de la neutropenia y disminuyen el tiempo de estancia hospitalaria 28,29 . En cuanto al tratamiento de los episodios de neutropenia febril, este se realizó acorde a las consideraciones internacionales.…”
Section: Discussionunclassified
“…22 The remission status was assessed after completion of each course of induction treatment, after the end of consolidation, before every two maintenance courses and every 3 months after the end of maintenance, or after HSCT, unless earlier bone marrow examinations were indicated by peripheral blood changes inconsistent with CR.…”
Section: Criteria For Responsementioning
confidence: 99%
“…Five of the included studies used G-CSF and two used GM-CSF (20)(21)(22)(23)(24)(25)(26). The commonly used dosage of G-CSF and GM-CSF is 5 µg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 6 studies reported on neutropenia duration (20)(21)(22)(24)(25)(26). In these studies, neutropenia was defined as <0.5x10 9 /l neutrophils.…”
Section: Number Of Patients With Infection and Severe Infectionmentioning
confidence: 99%